Sistematización de las composiciones del músico empírico y popular Ing. Julio Becerra Minga, de la parroquia Guachanamá, cantón Paltas, provincia de Loja, y su incidencia en el desarrollo del patrimonio cultural. Período 2012-2013 - Figueroa Robles, Lucia Margarita (2015)
Contributing to the rescue of popular musicians and empirical of the province of Loja, this research he focused on exalt the work of the composer Ing. Julio Becerra, native to Guachanama, by spreading his scores morphologically structured textual analysis, according to the objectives. A survey was conducted in the population, delimiting a shaped by the composer universe, whom the interview was applied, and the survey 352 residents. These techniques led to conclusion: The systematic works, organized and structured, positive impact on the cultural development of a people. Faced with what is expected to raise awareness among authorities about the importance of compositional output, to provide support and promotion. Through the hypothetical-deductive method two hypotheses of the contribution provided by the composer to heritage and cultural development of a people is raised. The Scientific Method allowed to raise the problem and gather background in quantitative and qualitative. Historical and Ethnographic method allowed to interact with the community; and the Analytical Method - Synthetic scores were analyzed. The proposed guidelines were socialized, allocating the product brochure elaborate.